جينيالوجيا الشعر الجزائري المعاصر مرحلة التسعينيات أنموذجا - ماي, أمال (قــــــراءات, 2019)
الملخص بالعربية: تتناول هذه القراءة التحولات الفكرية في النص الشعري الجزائري المعاصر الذي يبطن هاجس القلق وسؤال الهوية، و يعكس البنية الذهنية/ الفكرية التي شكلت عبر بنية اللغة الاستعارية المنحرفة المجاوزة للوضع اليومي والسياسي والاجتماعي، مما يولد نوعا من المواءمة بين البنية الفكرية والطموح الشعري. وعليه ستركز هذه القراءة على إثارة جملة من الإشكالات التي لا ندعي الإجابة عنها ولكن بغية فتح الأبواب لأبحاث لاحقة. *كيف واكب الشاعر الجزائري تلك التحولات الفكرية التي عصفت بالجزائر في مرحلة التسعينيات؟ *وهل استطاع الشاعر الجزائري مواكبة الحداثة في ظل التقلبات السياسية والاجتماعية التي ألمت بالبلاد؟ *هل يمكن لنص يتيم ضائع الجينيالوجيا وفاقد الهوية والخصوصية في مراحله الأولى أن يواكب الركب الحضاري و يعبر عن ذاته بأساليب تستند إلى التراث من جهة و تعتمد على التيمات الحداثية الشعرية من جهة أخرى؟؟ الملخص باللغة الإنجليزية: Dealing with this reading of intellectual transformations in contemporary poetic text Algerian who line the obsession of anxiety and the question of identity, and reflects the structure of the mental/ intellectual formed through Alastaaria devieant language situation daily and the political and social structure, which generates some sort of alignment between the intellectual infrastructure and ambitious poetic. And it will focus on the excitement of reading a number of problems that do not pretend to answer, but in order to open the doors for research on subsequent establishment of God. How accompanied Algerian poet those intellectual transformations that engulfed Algeria in the nineties stage? And is able to keep up with the Algerian poet modernity in light of the political and social fluctuations that have affected the country? Can text orphan Djinieloggie lost privacy and identity in the early stages to keep pace with civilization behind and expresses itself in ways that are based on the hand, and depends on the themes of modernist poetry on the other hand?